Nanohydroxyapatite Application to Osteoporosis Management. (28th October 2013) - Noor, Zairin
Abstract : Hydroxyapatite is chemically related to the inorganic component of bone matrix as a complex structure with the formula of Ca10 (OH)2 (PO4 )6 . Previous studies have reported the application of microsized hydroxyapatite to bone regeneration, but the result is not satisfied. The limitation comes from the size of hydroxyapatite. In addition, the duration of treatment is very long. The advantages of hydroxyapatite nanocrystal are the osteoconduction, bioresorption, and contact in close distance. Crystal in osteoporotic bone is calcium phosphate hydroxide with the chemical formula of Ca10 (OH)2 (PO4 )6 . Crystal of normal bone is sodium calcium hydrogen carbonate phosphate hydrate with the chemical formula of Ca8 H2 (PO4 )6 ·H2 O–NaHCO3 –H2 O. The recent development is applying nanobiology approach to hydroxyapatite. This is based on the concept that the mineral atoms arranged in a crystal structure of hydroxyapatite can be substituted or incorporated by the other mineral atoms. In conclusion, the basic elements of hydroxyapatite crystals, composed of atomic minerals in a certain geometric pattern, and their relationship to the bone cell biological activity have opened opportunities for hydroxyapatite crystals supplement application on osteoporosis. Understanding of the characteristics of bone hydroxyapatite crystals as well as the behavior of mineral atom in the substitution will have a better impact on the management of osteoporosis.